Border security barriers along the U.S. international border - Nunez-Neto, Blas (Nova Science Publishers, 2009)
Congress has repeatedly shown interest in examining and expanding the barriers being deployed along the U.S. international land border. The 109th Congress passed a number of laws affecting these barriers, and oversight of these laws and of the construction process may be of interest to the 110th Congress. The United States Border Patrol (USBP) deploys fencing, which aims to impede the illegal entry of individuals, and vehicle barriers, which aim to impede the illegal entry of vehicles (but not individuals) along the border. The USBP first began erecting barriers in 1990 to deter illegal entries and drug smuggling in its San Diego sector. The ensuing 14 mile-long San Diego "primary fence" formed part of the USBP's "Prevention Through Deterrence" strategy, which called for reducing unauthorised migration by placing agents and resources directly on the border along population centres in order to deter would-be migrants from entering the country. In 1996, Congress passed the Illegal Immigration Reform and Immigrant Responsibility Act which, among other things, explicitly gave the Attorney General (now the Secretary of the Department of Homeland Security) broad authority to construct barriers along the border and authorised the construction of a secondary layer of fencing to buttress the completed 14 mile primary fence. Construction of the secondary fence stalled due to environmental concerns raised by the California Coastal Commission. In 2005, Congress passed the REAL ID Act that authorised the Secretary of the Department of Homeland Security (DHS) to waive all legal requirements in order to expedite the construction of border barriers. DHS has announced it will use this waiver authority to complete the San Diego fence. The Secure Fence Act of 2006 directed DHS to construct 850 miles of additional border fencing. This requirement was subsequently modified by the Consolidated Appropriations Act, 2008 (P.L. 110-161), which was enacted into law on December 26, 2007. The act requires the Secretary of Homeland Security to construct fencing along not less than 700 miles of the south-west border. While the San Diego fence, combined with an increase in agents and other resources in the USBP's San Diego sector, has proven effective in reducing the number of apprehensions made in that sector, there is considerable evidence that the flow of illegal immigration has adapted to this enforcement posture and has shifted to the more remote areas of the Arizona desert. Nationally, the USBP made 1.2 million apprehensions in 1992 and again in 2004, suggesting that the increased enforcement in San Diego sector has had little impact on overall apprehensions. In addition to border fencing, the USBP deploys both permanent and temporary vehicle barriers to the border. Temporary vehicle barriers are typically chained together and can be moved to different locations at the USBP's discretion. Permanent vehicle barriers are embedded in the ground and are meant to remain in one location. A number of policy issues concerning border barriers generally and fencing specifically may be of interest to Congress, including, but not limited, to their effectiveness, costs versus benefits, location, design, environmental impact, potential diplomatic ramifications, and the costs of acquiring the land needed for construction.